2008
DOI: 10.1038/nature06874
|View full text |Cite
|
Sign up to set email alerts
|

Small phonon contribution to the photoemission kink in the copper oxide superconductors

Abstract: Despite over two decades of intense research efforts, the origin of high-temperature superconductivity in the copper oxides remains elusive. Angle-resolved photoemission spectroscopy experiments have revealed a kink in the dispersion relations (energy versus wavevector) of electronic states in the copper oxides at binding energies of 50-80 meV, raising the hope that this anomaly could be a key to understanding high-temperature superconductivity. The kink is often interpreted in terms of interactions between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
195
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(220 citation statements)
references
References 25 publications
23
195
1
1
Order By: Relevance
“…Also, the transport electron-phonon coupling is much smaller than its quasiparticle counterpart which provides a direct explanation of the observation that the resistivity is linear in T in the normal state above T c (Zeyher 1996). Recent local density approximation (LDA) calculations in YBCO (Heid et al 2008(Heid et al , 2009) and in LSCO (Giustino et al 2008) have found however, very small values of the coupling in the d-channel and conclude that the electron-phonon interaction is much too small to provide the glue for Cooper pair formation. Also quasiparticle mass enhancement factor renormalizations are small as is its transport counterpart.…”
Section: And Introducementioning
confidence: 99%
“…Also, the transport electron-phonon coupling is much smaller than its quasiparticle counterpart which provides a direct explanation of the observation that the resistivity is linear in T in the normal state above T c (Zeyher 1996). Recent local density approximation (LDA) calculations in YBCO (Heid et al 2008(Heid et al , 2009) and in LSCO (Giustino et al 2008) have found however, very small values of the coupling in the d-channel and conclude that the electron-phonon interaction is much too small to provide the glue for Cooper pair formation. Also quasiparticle mass enhancement factor renormalizations are small as is its transport counterpart.…”
Section: And Introducementioning
confidence: 99%
“…Previously it was reported that the nodal group velocity within 50 meV of Fermi energy (E F ) is independent of the cuprate family or the number of CuO 2 layers in the crystal unit cell, and it is almost constant across the entire phase diagram [2]. Recent ARPES technique with low-energy photons (hν = 6-8 eV) has extensively improved the momentum and energy resolutions [3,4], and uncovered a remarkable band renormalization very close to the E F (< 20 meV) [5][6][7][8][9][10], in addition to the well-studied kinks seen at 40-80The new fine band-feature (or "low-energy kink") determines the nodal Fermi velocity of Bi2212, thus it is crucial for the understanding of the electronic properties, which are dominated by the conduction electrons close to the E F .A recent theoretical study has suggested that coupling to phonons is too small to produce the observed band renormalization [11]. On the other hand, it has been pointed out that the strong electron correlation or reduced screening can significantly enhance the phononelectron coupling [10,[12][13][14][15].…”
mentioning
confidence: 99%
“…A recent theoretical study has suggested that coupling to phonons is too small to produce the observed band renormalization [11]. On the other hand, it has been pointed out that the strong electron correlation or reduced screening can significantly enhance the phononelectron coupling [10,[12][13][14][15].…”
mentioning
confidence: 99%
“…This instability results in the so-called BCS state (coherent state of Cooper pairs), that leads to a gap in the spectrum of excitations, responsible for superconductivity. In the currently available high-T C superconductors (the cuprates), an electron pairing is also thought to be realized through a mediating boson, although probably not the phonon [13]. Excitons have been proposed as suitable mediating bosons to achieve higher critical temperatures of superconductivity in specially designed heterostructures ([14], see [15] for a review).…”
mentioning
confidence: 99%